Pengaruh Inflasi, Nilai Tukar, dan Suku Bunga terhadap Indeks Harga Saham Jakarta Islamic Index (JII) Periode 2016-2023 - Syiffa, Miomi Ayu; Octovian, Reza (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This study aims to determine the effect of inflation, exchange rates and interest rates on the Jakarta Islamic Index stock price index for the period 2016-2023 partially or simultaneously. The research method and type of data used are quantitative methods and secondary data, while the sample in this study is using annual date series (time series) data from 2016-2023. The data analysis method used is financial ratio analysis and quantitative analysis. Furthermore, hypothesis testing uses the t test and f test. The results of this study indicate that Inflation partially has no effect on the share price of the Jakarta Islamic Index for the 2016-2023 Period, the Exchange Rate variable partially has a negative effect on the share price of the Jakarta Islamic Index for the 2016-2023 Period, Interest Rates partially have no effect on the share price of the Jakarta Islamic Index for the 2016-2023 Period. Inflation, exchange rates and interest rates simultaneously affect the share price of the Jakarta Islamic Index (JII) 2016-2023 period. Based on the results of the coefficient of determination test, the R square value is 0.887. So it can be concluded that the Inflation, Exchange Rate and Interest Rate variables have a large influence of 88.7% on the Jakarta Islamic Index Stock Price variable.